Implementation of level shifted PWM and bee algorithm for cascaded multilevel inverters - Sarala Kumari, G; Ganesh Babu, B; Kapoor, Rashmi; Ranjit, M (International Journal of Engineering and Technology, 2018)
This paper presents different modulation techniques to convert DC to AC voltage in multilevel inverter. In present scenario availability of fossil fuels are decaying day by day so importance of renewable energy sources are increasing for electric power generation. Solar energy is abandon in nature. The standalone solar PV system is used for water pumping system in Indian villages, where grid lines are not available.Cascaded H-bridge inverter (CHB) is suitable for renewable energy sources as it contains separate DC sources. The output voltage consists of predominant lower order harmonics. The various Sinusoidal PWM Techniques such as PD, POD and APOD were used to minimize the THD; it is a high switching frequency technique. Due to high switching frequency, high switching losses are occurred so filter requirement is more. To avoid this problem low switching frequency technique is used. The Selective Harmonic Elimination-Pulse Width Modulation (SHE-PWM) technique is utilised to eliminate the lower order harmonics and also to reduce the THD in multilevel inverters by solving the nonlinear equations. The non linear equations are solved by determining the proper switching angles using Bee algorithm. Bee algorithm is a metaheuristic nature inspired algorithm, based on the foraging behavior of honey bees. Simulation is carried out by using the MATLAB/SIMULINKK software for [5-7]-levelsÂ Â